Subclinical inflammatory response after accelerated corneal cross-linking - HashemiHassan; AshrafNahid; JafarzadehpurEbrahim; HedayatfarAlireza; AsgariSoheila (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
Background: To evaluate the inflammatory response after accelerated collagen cross-linking (CXL) in eyes with keratoconus. Methods: Consecutive eyes with keratoconus undergoing CXL surgery were included in this non-randomized interventional study. Aqueous flare was measured pre- and post-operatively with a laser flare photometer at 1 week, 1, 3 and 6 months after CXL. Results: Sixty eyes of 60 patients were entered into the study. Before CXL, the mean flare value was 4.5 photons per millisecond (ph/ms). The flare values observed at week 1 (7.1 ph/ms; P=0.008), month 1 (6.5 ph/ms; P=0.04), month 3 (6.7 ph/ms; P=0.004) and month 6 (6.7 ph/ms; P=0.004) were significantly higher compared to baseline. Flare values were not significantly different from week 1 up to 6 months after CXL (P=0.930). No statistically significant correlation was detected between the amount of inflammation and keratometric indices. Conclusions: Accelerated CXL in patients with keratoconus may cause a subclinical inflammatory response which is evident as slight but rather long-lasting rise of aqueous flare.